The Impact of Sick Building Syndrome and Physical Air Quality on Staff Productivity in the Hospital's Outpatient Room of Rumah Sakit Umum Daerah Haji Indonesia - Drastyana, Serlly Frida; Silvia Catalan Ambag; Ningrum, Listiana Dewi Widya; Diah Wijayanti Sutha (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: The concept of SBS as an occupational health problem is related to air pollution, inadequate ventilation, and indoor air quality in office buildings. Lighting in the RSUD Haji Building still does not meet general and local lighting standards. Complaints of eye fatigue are also felt by administrative staff in the outpatient room of the RSUD Haji Indonesia. This research aimed to examine how physical air quality and sick building syndrome give impact to officer productivity in the outpatient room of the RSUD Haji Indonesia. Methods: This kind of study used a cross-sectional design and was observational. Simple random sampling was utilized in the sampling process, and logistic and linear regression were used to analyze the data. Results and Discussion: Lighting in outpatient rooms that is 100% compliant with standards. The percentage of rooms without proper temperature norms was 21.42%. The rate of rooms with inadequate noise requirements was 17.86%. Spaces without 50% relative humidity norms. SBS symptoms: 10.3% of respondents said they always had itchy skin, and 27.6% said they frequently experienced extreme stress and exhaustion symptoms. Conclusion: There was no effect of temperature, lighting, or noise in the room regarding the sick building syndrome symptoms of officers in the outpatient room, except humidity. However, most workers felt SBS symptoms. Officer productivity was not impacted by the physical quality of the air or by sick building syndrome symptoms.